Logistics commitment: an evidence of long-term relationship on sustainable global supply chain. - Sidah Idris; Suhana Mohezar (Science Publishing Corporation, 2018)
Manufactures and all network partners may think that global supply chains are simple and direct. But, in the vast majority of cases, this isnot the case. Customer demand is supported by complex and lengthy global supply chain. The intermodal transportations provide the keysuccess of the connections between global factories and along the supply chain parties. While they provide critical services, each level oftransportation will present challenge and difficulty to all parties. This study look on how logistics commitment can improves operatingefficiencies among local manufacturers and service providers as they are in global supply chain network. And, how each intermodal invested improve capabilities, creating reliable and economical port-to-destination delivery services in ensure good relationship with theirpartners. The study aims is to identify how the service providers can reshape relationship and revise networks to maintain smooth andefficient global logistics flows. This empirical study will use survey questionnaire to get the answer for each question and utilize PartialLeast Square (PLS) to analyse the data. Result shows how logistics commitment effort and strategy as to sustain global supply chainrelationship.